Self-Determination and Academic Motivation among Nursing Students in their Transition to Face-to-Face Learning in Selected Higher Education in Quezon City, Philippines: A Sequential Explanatory Design - Dalida, Cesar M; Dy, Dyrly Dyezebel C; Fermin, Allan F; Fermin, Elsie L; Guido, Luche B; Juane, Edward Jeremy V; Flores, Michael John V (Al-Hijrah Indonesia, 2025)
Background: The COVID-19 pandemic has significantly impacted the educational landscape, leading to the adoption of virtual learning in the Philippines. Purpose: This study aimed to identify students' self-determination and academic motivation following virtual learning and their experiences transitioning to face-to-face learning in selected higher education institutions in Quezon City, Philippines. Methods: The study employed a Mixed-type research approach, specifically the Sequential Explanatory Research Design, with a sample size of 148 nursing students in District 5 in Quezon City. Results: A high level of self-determination was found among participants, significantly correlating the type of family. Three subscales were identified regarding academic motivation: Mastery, Performance Approach, and Performance Avoidance. Participants displayed high motivation in the Mastery subscale, moderate motivation in Performance Avoidance, and lower motivation in Performance Approach. The study established a strong association between self-determination and academic motivation, suggesting that a student with self-determination is likely to be academically motivated, while academic motivation can help develop self-determination. Qualitative analysis revealed three themes: Multifaceted Feelings, Transformative Shift, and Relational Pillars, illustrating the emotional complexities, physical and psychological changes, and the crucial role of support systems during the transition. Conclusions: The study highlights the importance of considering self-determination and academic motivation in understanding students’ experiences during the transition to face-to-face learning. The findings provide insights into this transition’s emotional and adaptive aspects, emphasizing the interconnectedness of personal relationships with academic resilience.